Association of the Paediatric Admission Quality of Care score with mortality in Kenyan hospitals: a validation study - Opondo, C; Allen, E; Todd, J; English, M (Elsevier, 2018)
Background: Measuring the quality of hospital admission care is essential to ensure that standards of practice are met and continuously improved to reduce morbidity and mortality associated with the illnesses most responsible for inpatient deaths. The Paediatric Admission Quality of Care (PAQC) score is a tool for measuring adherence to guidelines for children admitted with acute illnesses in a low-income setting. We aimed to explore the external and criterion-related validity of the PAQC score by investigating its association with mortality using data drawn from a diverse sample of Kenyan hospitals. Methods: We identified children admitted to Kenyan hospitals for treatment of malaria, pneumonia, diarrhoea, or dehydration from datasets from three sources: an observational study, a clinical trial, and a national cross-sectional survey. We extracted variables describing the process of care provided to patients at admission and their eventual outcomes from these data. We applied the PAQC scoring algorithm to the data to obtain a quality-of-care score for each child. We assessed external validity of the PAQC score by its systematic replication in datasets that had not been previously used to investigate properties of the PAQC score. We assessed criterion-related validity by using hierarchical logistic regression to estimate the association between PAQC score and the outcome of mortality, adjusting for other factors thought to be predictive of the outcome or responsible for heterogeneity in quality of care. Findings: We found 19 065 eligible admissions in the three validation datasets that covered 27 hospitals, of which 12 969 (68%) were complete cases. Greater guideline adherence, corresponding to higher PAQC scores, was associated with a reduction in odds of death across the three datasets, ranging between 9% (odds ratio 0·91, 95% CI 0·84–0·99; p=0·031) and 30% (0·70, 0·63–0·78; p<0·0001) adjusted reduction per unit increase in the PAQC score, with a pooled estimate of 17% (0·83, 0·78–0·89; p<0·0001). These findings were consistent with a multiple imputation analysis that used information from all observations in the combined dataset. Interpretation: The PAQC score, designed as an index of the technical quality of care for the three commonest causes of admission in children, is also associated with mortality. This finding suggests that it could be a meaningful summary measure of the quality of care for common inpatient conditions and supports a link between process quality and outcome. It might have potential for application in low-income countries with similar disease profiles and in which paediatric practice recommendations are based on WHO guidelines.